Prevalence and genetic subtypes of congenital myasthenic syndromes in the pediatric population of Slovenia. (May 2020) - Troha Gergeli, Anja; Neubauer, David; Golli, Tanja; Butenko, Tita; Loboda, Tanja; Maver, Aleš; Osredkar, Damjan
Abstract: Aim: Congenital myasthenic syndromes (CMS) are rare, genetically and phenotypically diverse disorders of neuromuscular transmission. Data on prevalence among children are scarce. Whole exome sequencing facilitated discovery of novel CMS mutations and enabled targeted treatment. Our aim was to identify the prevalence, genetic subtypes and clinical characteristics of CMS in pediatric population of Slovenia. Methods: In this observational, national, cross-sectional study, medical records were retrospectively reviewed. Children with genetically confirmed CMS, referred over a 19 – year period (2000–2018) to the University Medical Centre, Ljubljana, Slovenia, were included in the study. Genetic and phenotypic characteristics were collected and prevalence of CMS in children was calculated. Results: Eight children with a confirmed genetic mutation in 5 different genes (CHRNE, CHRND, RAPSN, CHAT, MUSK) causative of the CMS were identified. Calculated prevalence of genetically confirmed CMS was 22.2 cases per 1.000.000 children at the end of 2018. Interpretation: The prevalence of genetically confirmed CMS in Slovenian children at the end of 2018 exceeds previously reported prevalence by more than two-fold, which suggests that prevalence in the literature is likely to be underestimated. Two extremely rarely detected mutations in MUSK and CHRND gene were detected and patient's clinical descriptions add important information on genotype-phenotype correlation. Highlights: The prevalence of CMS in Slovenian children exceeds previously reported data by more than two-fold. CMS is often a missed diagnosis and prevalence is likely to be underestimated. Electrophysiological testing (RNS-EMG) often gave false negative results in the first year of life in our cohort. Genetic molecular testing has improved diagnostics and enabled more targeted treatment. Disease awareness among healthcare professionals and reliable diagnostic tests are important.